Penataan Sistem Informasi Penjualan Pakaian Berbasis Web - Dino Septian Adi; Maftucha Putri (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2023)
The development of information technology is increasingly rapidly, one of which is Internet technology. The existence of the internet today is very influential in the world of business and industry, large and small. The dependence of the world of business and industry on the internet is getting higher day by day. The development of internet technology as an information medium that can be accessed using computers connected to various parts of the world, so that access to information can be done anywhere so that it is not limited by space and time.